Doing, Teaching, Learning and Thinking About Mathematics – On Becoming a Transformative Teacher - Pant, Binod Prasad (Journal of Education and Research, 2017)
I solved many mathematical problems till today - countless academic problems inside the classroom, and a few pragmatic problems outside. At the beginning of my teaching career, I spent significant time convincing my students that mathematics teaching is an algorithmic problem solving of routine mathematical items to get the correct answers. Afterwards, I slowly took a shift from doing mathematics to teaching mathematics, identifying lots of tricks, tips and techniques. I spent more than a decade to train myself with better techniques to become a better mathematics teacher seeking better achievements of students in written tests. Later on, I engaged myself as a math learner and sought the significance of the methods I employed to teach the mathematical concepts, relation, and logics. I am now at the crossroads of searching better alternatives that help students learn mathematics in a meaningful way. I frequently ask myself why I am teaching mathematics. What does a good mathematics teacher mean? What we do is largely guided by what we believe. Questioning on the widely accepted assumptions, examining the deep-rooted beliefs for the positive shift, and highlighting the epiphanies of my professional life could be very essential on becoming a transformative teacher. In this paper, I portray my narratives as a student and as a mathematics teacher to explain my shift towards becoming a transformative teacher. Through my verisimilitude narratives, I invite readers to examine their beliefs and practices on teaching mathematics, and envisage for better alternatives being aware of their limitations and contexts.